Study on the Influence of Local High Steps on the Uniformity of Global Critical Dimension in Implant Layers - WANG Qiang; WU Tingxi; SONG Shuaidi (Nantong Daxue xuebao. Ziran kexue ban)
In the processes of integrated circuits fabrication, the distribution of high steps in implant layers is one of the critical factors that affects the uniformity and quality of implant-layer photoresist critical dimension(CD). Based on the study of the distribution, density, width and the distance from the exposure patterns to the high steps on the wafer are studied, the key high-step parameters that affect the CD uniformity are found, and an optimized layoutdesign method is proposed. The experimental results reveal that the CD uniformity is improved with the high steps distributed uniformly. The step density has little effect on the CD uniformity; the larger the step width is, the smaller the average value of CD is, but there is no obvious effect on the value of 3σ; the farther the distance between the high steps and the exposure patterns is, the better CD uniformity is. After applying the optimized layout-design method, the CD uniformity of devices and the stability of production are improved. The CD uniformity of implant layers lithography is increased by 49.4%.